Ritual as a Connecting Link of Two Realities of Personality - Mikayelyan, Erik (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
Considering the ritual activity of the person in the obsessional neurosis as a result of the superposition of two realities – the objective (social) and magic (archaic), we pay attention to the neurotic side of this process. We can consider this aspect as a result of violations of the interaction of the individual with the social environment, as a violation of the individual-adaptive system. Repetition of pathological functional structures can be seen in ritual actions which are not adequate to objective reality.
Keywords: ritual, reality, personality, neurosis, meaning, compulsive rituals, self-image, directivity, the psychic life